Effects of feeder design and pelleting on growth performance and water use in finishing pigs - Rantanen, M.M.; Hines, Robert H.; Kim, I.H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed from wet-dry feeders had 4% greater ADG with 50% less water usage than those consuming feed from dry feeders. Pelleting diets improved F/G by 4% compared to meal diets. However, the benefits of pelleting were primarily when a dry feeder was used, with little evidence to support use of both pelleting and wet/dry feeders for finishing pigs.
Keywords: Swine; Finishing pigs; Feeders; Pellet